(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the entomophages of pests of vegetable and melon crops taxonomically, based on entomological methods. Studies have shown that in this region there are 72 species from 17 families belonging to 5 families of dominant entomophages. The entomofauna of Central Fergana has a high proportion of desert-specific species and native species, but the exchange of adventitious or allochthonous species is slow. Natural insects of vegetable and melon crops are 8 species belonging to 5 families of the genus Hemiptera, 21 species of 6 families of Hymenoptera, 27 species of Coleoptera - 2 families, 4 species of Neuroptera - 1 family and 12 species of 4 families Diptera. Of the natural fighters identified in pests of vegetables and melons, 19 species have a high incidence, 22 species are common, and the remaining 31 species are rare or random. 6 species of entomophages are monophages, 31 species are oligophages and 35 species are polyphages. These are 41 species of predators and 31 species of parasites, depending on whether they feed on the host organism or prey.